Comparative Analysis of Amino Acids, Nucleosides, and Nucleobases in Thais clavigera from Different Distribution Regions by Using Hydrophilic Interaction Ultra-Performance Liquid Chromatography Coupled with Triple Quadrupole Tandem Mass Spectrometry - Yahui Ge; Yuping Tang; Sheng Guo; Xin Liu; Zhenhua Zhu; Pei Liu; Jin-ao Duan (International Journal of Analytical Chemistry)
Thais clavigera, as function food, is distributed widely along the coasts of China. To compare and tap its potentially nutritional and functional values, hydrophilic interaction ultra-performance liquid chromatography coupled with triplequadrupole tandem mass spectrometry (HILIC-UPLC-TQ-MS/MS) was used for simultaneous identification and quantification of amino acids, nucleosides, and nucleobases in the extracts of T. clavigera from 19 sea areas in China, and a PCA was further performed for comparing their content variation in different distribution regions. The total contents of amino acids varied from 116.74 mg/g to 298.58 mg/g being higher than contents of nucleosides and nucleobases that varied from 2.65 mg/g and 20.49 mg/g. Among the habitats, Hainan province had content advantages on others. By PCA, samples collected from different regions were classified into three groups. For specific constituents, lysine accounted for large part of essential amino acids; glycine and taurine also play important roles in the delicate taste and health care function of it. Inosine takes up most of total contents of nucleosides and nucleobases. These results provided good data for establishing quality standard of T. clavigera related products and their further development and utilization.